Associação entre sintomas ansiosos e depressivos e variáveis clínicas em pacientes obesos candidatos a cirurgia bariátrica - Heberle, Luiza Schmidt (2015)
Background: Obesity and psychiatric disorders are likely to exert considerably negative impact on the quality of life of patients. In this regard, one may observe a high incidence of anxiety disorders in obese patients, particularly among candidates for bariatric surgery. Anxiety and depressive symptoms, as well as substance abuse are a substantial threat to successful results following bariatric surgery. Objectives: To evaluate the association between the intensity of anxiety symptoms and body mass index, depressive symptoms and alcohol and tobacco use in obese patients who apply for bariatric surgery. Setting: Centro da Obesidade Síndrome Metabólica, Pontifícia Universidade Católica do Rio Grande do Sul, Porto Alegre, Brazil. Methods: Cross-sectional study involving 425 patients that have applied to bariatric surgery. Levels of anxiety and depression were assessed by the Beck Anxiety Inventory and the Beck Depression Inventory. Alcohol use was assessed by Alcohol Use Disorders Test and tobacco use by the Fagerström Test of Nicotine Dependence. Results: Among the 425 patients, 33.4% scored BAI above the cut-off point, while 59.3% scored BDI above the cut-off point. There was a significant statistic association between anxiety and depressive symptoms (P <0.001). There was a statistically significant, direct and weak correlation between BAI scores and BMI. No patient presented AUDIT above the cut-off point and 4.7% were smokers. Conclusions: The high prevalence of anxiety and depressive symptoms detected is alarming and shows how much bariatric surgery candidates are subject to emotional suffering. The low prevalence of alcohol and tobacco use confirms findings of other studies.